Review of Investigation on Distributed Control of Islanded Micro Grid - Kanathe, Manish; Tripathi, Shiv (International Journal of Computer Sciences and Engineering, 2019)
In the hierarchical control of an islanded microgrid, secondary control could be centralized or distributed. The former control strategy has several disadvantages, such as single point of failure at the level of the central controller as well as high investment of communication infrastructure. In this paper three-layer architecture of distributed control. The agent layer is a multi-agent system in which each agent is in charge of a distributed generation unit. Due to communication network constraints, agents are connected only to nearby neighbors. However, by using consensus algorithms the agents can discover the required global information and compute new references for the control layer. In this paper, a review of distributed control approaches for power quality improvement is presented which encompasses harmonic compensation, loss mitigation and optimum power sharing in multi-source-load distributed power network.